EFFECTS OF BLOOD FLOW RESTRICTION IN LARGE AND SMALL MUSCLE GROUPS - Clael,Sacha (2021)
ABSTRACT Introduction It is known that strength training brings improvements in health and sports performance by causing muscle hypertrophy and increased strength, as well as modifying some hemodynamic and physiological factors. Several strength training methodologies have been developed, one of which is vascular occlusion. There are few studies with large muscle groups due to poor adherence to the training style and the fact that vascular occlusion of large muscle groups is more difficult. Objective To verify and compare the hemodynamic effects of exercise with and without vascular occlusion in different muscle groups. Methods Quantitative crossover study, with cross-sectional and field procedures. The sample consisted of 10 physically active healthy male and female subjects between 18 and 30 years of age. With the cross-over design, all the volunteers participated in 3 groups: intervention with vascular occlusion, intervention without vascular occlusion and the control group. Results Overall, lactate and cholesterol remained elevated after 15 minutes of recovery and blood glucose and blood pressure did not vary among the groups. Conclusion Vascular occlusion training is an effective method for manipulating hemodynamic variables. Evidence level II; Clinical study.